ANALISIS TEKNIK DASAR PERMAINAN FUTSAL ATLET SIBA FC LUBUKLINGGAU - Alpiansyah; Wawan Syafutra; Hengky Remora (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
This research aims to determine the results of an analysis of the basic techniques of playing futsal. In this research problem, the basic technical skills of futsal players are not yet known. This type of research uses a qualitative descriptive method. The population in this study were all 14 SIBA FC Lubuklinggau athletes. The sampling technique used simple random sampling, so the sample in this study was 14 people. The test instruments used are observation, interviews, documentation and questionnaires, which consist of passing, dribbling, shooting and control. The data was analyzed using a scale formula of 5 categories: very good, good, fair, poor and very poor. Based on the results of the basic futsal playing skills test of 14 people, it was found that 3 people got very good, 10 people got good and 1 person got fair marks. So it can be concluded that the basic technical skills of SIBA FC Lubuklinggau athletes' futsal players are in the good category